Comparative Study of Effect of Fin Arrangement on Propulsion Performance of Bio-Inspired Underwater Vehicles with Multiple SMA Fins. (30th September 2015) - He, Jian-hui; Zhang, Yong-hua; Low, Kin-huat
A biologically inspired underwater vehicle (BIUV) was built using multiple lightweight bio-inspired shape memory alloy (SMA) fins. An unsteady 3D computational fluid dynamics (CFD) method using an unstructured, grid-based, and unsteady Navier-Stokes solver with automatic adaptive re-meshing was adopted to compute unsteady flow. The hydrodynamics of multiple fins at a certain Reynolds number (Re = Uc/v, where U is the upstream flow velocity, c is the chord length, and v is the kinematic viscosity) was studied and simulated using CFD to estimate hydrodynamic forces and characterize flow and vortex patterns created by the fins. Two common arrangements of multiple fins on the BIUV were considered: a posterior fin that is parallel to the anterior fins (case 1) and a posterior fin that is perpendicular to the anterior fins (case 2). First, the influence of the distance between two anterior undulating fins on the propulsion performance of both arrangements of multiple fins on the BIUV was investigated. The effect of the distance between the anterior undulating fins and the posterior oscillating fin was also analysed. The length of the posterior oscillating fin was varied and the fin surface area was held constant (24 mm 2 ) to illustrate the influence of this parameter. Finally, the effect of frequency, amplitude, and wave number of anterior undulating fins on the non-dimensional drag coefficient of the posterior oscillating fin was investigated. Based on the flow structures, the reasons for the different performances of the BIUV are discussed. BIUV performances largely depend on the arrangements of multiple fins and the gap between the fins. Dimension and kinematic parameters also affect the performance of the BIUV. The results provide a physical insight into the understanding of fin interaction in fish or BIUVs that are propelled by multiple fins.